Thermodynamic Analysis of Double-Stage Compression Transcritical CO2 Refrigeration Cycles with an Expander - Zhenying Zhang; Lirui Tong; Xingguo Wang (Entropy, 2015)
Four different double-compression CO2 transcritical refrigeration cycles are studied: double-compression external intercooler cycle (DCEI), double-compression external intercooler cycle with an expander (DCEIE), double-compression flash intercooler cycle (DCFI), double-compression flash intercooler cycle with an expander (DCFIE). The results showed that the optimum gas cooler pressure and optimum intermediate pressure of the flash intercooler cycles are lower than that of the external intercooler cycle. The use of an expander in the DCEI cycle leads to a decrease of the optimum gas cooler pressure and little variation of the optimum intermediate pressure. However, the replacement of the throttle valve with an expander in the DCFI cycle results in little variation of the optimal gas cooler pressure and an increase of the optimum intermediate pressure. The DCFI cycle outperforms the DCEI cycle under all the chosen operating conditions. The DCEIE cycle outperforms the DCFIE cycle when the evaporating temperature exceeds 0 °C or the gas cooler outlet temperature surpasses 35 °C. When the gas cooler exit temperature varies from 32 °C to 48 °C, the DCEI cycle, DCEIE cycle, DCFI cycle and DCFIE cycle yield averaged 4.6%, 29.2%, 12.9% and 22.3% COP improvement, respectively, over the basic cycle.